92.0k views
3 votes
3(2x - 7) = 5(x + 3) + 2x7​

2 Answers

3 votes
That would equal to 50 or x=50
User Falomir
by
5.3k points
4 votes

Answer:

x = -1.52016

Explanation:

Step 1: Write equation

3(2x - 7) = 5(x + 3) + 2x⁷

Step 2: Solve for x

  1. Distribute: 6x - 21 = 5x + 15 + 2x⁷
  2. Subtract 6x on both sides: -21 = -x + 15 + 2x⁷
  3. Add 21 to both sides: 0 = -x + 36 + 2x⁷
  4. Rearrange: 0 = 2x⁷ - x + 36
  5. Find roots by graphing: x = -1.52016
3(2x - 7) = 5(x + 3) + 2x7​-example-1
User Umop
by
6.1k points